Analisis Implikasi AI Terkait Manajemen Waktu dan Produktivitas Siswa dalam Proses Pembelajaran Kelas - Septiana Mulyani; Abdurahman Hakim Fatoni; Agus Wedi (STAI AL-AMIN, 2025)
This study aims to analyze the use of AI related to time management and student productivity in the learning process of class V at SDN Lawangan Daya 2 Pamekasan. Which is motivated by the advancement of technology and information, so that teachers are encouraged to use innovative, effective, and efficient learning media that are used to increase students' enthusiasm for learning. Therefore, researchers conducted research and analyzed how the implications of AI are related to time management and student productivity in the learning process of class V at SDN Lawangan Daya 2 Pamekasan. The type of research used is a Qualitative approach with Data Collection Techniques through Observation, Interviews, and Documentation directly to the field. After that, the collected data was analyzed through several more stages, namely the collection, presentation, and conclusion stages. The results of the study showed that most of the results of the implications of AI related to time management and student productivity in the learning process had a fairly good level of influence on students and teachers, although there were still some students and teachers who still needed special attention in terms of the learning process using AI. This research is expected to be a reference for other teachers that the use of AI in learning is important, especially in the use of learning media which has a significant influence on the results of the learning process.